2006
DOI: 10.1016/j.jvs.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Acute intramural hematoma of the aorta: A mystery in evolution

Abstract: Thrombosis is the endpoint of atherosclerosis and inflammation is linked to the development of atherosclerosis. This study suggests that CD40-CD40L interactions may be one molecular mechanism linking the inflammation and the thrombosis associated with atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 21 publications
1
55
0
5
Order By: Relevance
“…The IRAD reports 58/1040 (5.7%) dissections were, in fact, IMHs. 29 Song et al, 30 however, reported a 28.3% rate of IMHs in their series.…”
Section: Differential Diagnosis Of Taadmentioning
confidence: 87%
“…The IRAD reports 58/1040 (5.7%) dissections were, in fact, IMHs. 29 Song et al, 30 however, reported a 28.3% rate of IMHs in their series.…”
Section: Differential Diagnosis Of Taadmentioning
confidence: 87%
“…With an FDR of 0 and by applying a minimal fold change of 2, the analyses revealed consistent patterns of differential gene expression. Thus, a total of 623 genes were found to show 302 Vascular and Endovascular Surgery 46 (4) altered expression in patients with type B AD compared with controls, of which 220 genes were upregulated and 403 genes were downregulated ( Figure 2B). …”
Section: Microarray Analysismentioning
confidence: 99%
“…It is proposed that bleeding of the vasa vasorum represents the first step of dissection process. 3,4 The Stanford classification distinguishes AD into type A or type B, depending on whether the site of the initial tear is in the ascending or descending arms of the aorta, respectively. Almost 60% of reported cases of AD are type A and 40% type B.…”
Section: Introductionmentioning
confidence: 99%
“…Its true incidence is difficult to determine but is estimated to vary between 2% and 8% of all acute aortic syndromes. [2][3][4] According to the classification by Svensson et al 5 (Table), PAU and IMH can be considered as variants of the classical double-barrel aortic dissection. They occur more often in the descending aorta as opposed to classical dissections.…”
Section: ¤ ¤mentioning
confidence: 99%